2016
DOI: 10.3109/15569527.2015.1124886
|View full text |Cite
|
Sign up to set email alerts
|

Long-term intraocular pressure changes after intravitreal injection of bevacizumab

Abstract: Our results suggest that under long-term monitoring, with a treat-and-extended regimen, intravitreal bevacizumab injections were associated with sustained IOP elevation. In particular, multiple intravitreal injections could be associated with sustained IOP elevation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 30 publications
2
21
2
2
Order By: Relevance
“…There were five RCTs1920212223 and 17 non-RCT studies1415161724252627282930313233343536. The latter group included 11 retrospective case series1417242526272829303132, two prospective studies3334, and four post hoc analyses15163536. Follow-up in the included articles ranged from 2.2627 to 6031 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were five RCTs1920212223 and 17 non-RCT studies1415161724252627282930313233343536. The latter group included 11 retrospective case series1417242526272829303132, two prospective studies3334, and four post hoc analyses15163536. Follow-up in the included articles ranged from 2.2627 to 6031 months.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven retrospective1417242526272829303132 and two prospective3334 studies, which reported the case numbers and incidence rates of SE-IOP among the 5062 subjects, were analyzed. Prevalence of SE-IOP varied from 1.6% (5 of 302 cases) to 11% (22 of 201 case), with a pooled prevalence (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Over the years, several other studies have been published with varying numbers of patients reporting the prevalence of longterm IOP increase after treatment with bevacizumab, ranibizumab or aflibercept injections. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] One of the studies with the largest number of patients (retrospective analysis of VIEW 1 and 2 study data from a total of 2457 patients) showed a significantly higher IOP increase in eyes after ranibizumab treatment than in patients after aflibercept treatment. 31 In 2016 Zhou et al conducted a meta-analysis of 5 randomized controlled trials (RCT) in 1428 patients and 8358 patients from 17 non-RCTs.…”
Section: Possible Side Effects From Intravitreal Injections Elevated mentioning
confidence: 99%
“…Kurzfristige Druckanstiege sind auch hier durch die reine Volumenzunahme unmittelbar post injectionem erklärt. Darüber hinaus gab es in der jüngeren Vergangenheit einige Publikationen, die über eine erhöhte Prävalenz andauernder Druckanstiege (Häufigkeit 6-11 %) nach multiplen Anti-VEGF-Injektionen berichteten [15][16][17]. Eine Reihe möglicher Risikofaktoren für dieses Phänomen wurden benannt: Zahl der Injektionen, Abstand zwischen den Injektionen unter 8 Wochen, bekanntes Glaukom, retinaler Venenastverschluss.…”
Section: Augendrucksteigerung Nach Intravitrealer Okulärer Medikamentunclassified